Tribal Relation to Spatio-Temporal Variation of Wild Mushrooms in Eastern Lateritic Part of India - Manna, Sumit; Ray, Debal; Roy, Anirban (Ethnobotany Research and Applications, 2014)
Mushroom is one of the most significant biodiversity components for both ecological and economic point of view. It deserves not only the good sources of nutrients, medicine but also has key function in nutrient recycling and niche for several animal resources. Eastern lateritic part of India with its distinct seasonality and undulated topography, harbours mosaic macro fungal resources on the forest floors with distinct spatio-temporal variation. Among 18 species related to tribal use, the most usable species were Astraeus hygrometricus Amanita vaginata var. alba, Amanita banangiana, Russula Nigerians, Termitomyces eurhizus, Termitomyces microcarpus etc. During monsoon and post monsoon period, second half of August is the optimum time for 11 wild edible mushrooms. Out of total production 47.2% production was taken place at that time. These regions with its tribal population, especially the Santals in the forest fringes, were very potential for traditional knowledge related to mushrooms. This paper deals with ethnic pattern of utilization in relation to spatio-temporal distribution of macro fungal diversity, its habitat and traditional tribal knowledge in ecology, use and others.